Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top


I tried letting $x=\tan\theta\ $ where $\frac{-\pi}{2} < \theta < \frac{\pi}{2}$ so that $dx = \sec^2\theta\,d\theta$ and after making the substitution one gets to $$\int\frac{\sec^3\theta}{\tan\theta} d\theta$$ which is equivalent to $$\int\frac{1}{\cos^2\theta\sin\theta}d\theta$$

After this, I don't know how to proceed. I tried looking for the same integral elsewhere and I found a solution that involves a method called partial fraction decomposition, I believe. But, I have not been taught that method yet and this integral appears on the section of the book that I am currently working on.

share|cite|improve this question
Because of the shape of the answer, either we come up with a magic substitution (can be done, but artificial), or we end up with partial fractions. Something that works fairly nicely is $x^2+1=t^2$. Then $x\,dx=t\,dt$, so $\frac{dx}{x}=\frac{t\,dt}{x^2}=\frac{t\,dt}{t^2-1}$. We end up with $\int \frac{t^2\,dt}{t^2-1}$. So we are integrating $1+\frac{1}{t^2-1}$. – André Nicolas Jan 3 '13 at 1:28
up vote 9 down vote accepted

The best way would be to start with André Nicolas' substitution. But I will take it from where you left it. So far, I can't see how to avoid partial fraction decomposition (Edit: Now I see, and you got it).

We can rewrite the integrand as follows: $$ \frac{1}{\cos^2\theta\sin\theta}=\frac{\sin\theta}{\cos^2\theta\sin^2\theta}=\frac{\sin\theta}{\cos^2\theta(1-\cos^2\theta)} $$ Now we just have to use the substitution $u=\cos\theta$. This yields the integral of a rational function. Namely $$ \int \frac{- du}{u^2(1-u^2)}=\int \frac{du}{u^2(u^2-1)} $$ After decomposition into partial fractions, one has $$ \int \left(-\frac{1}{u^2}+\frac{1/2}{u-1}-\frac{1/2}{u+1}\right)du=\frac{1}{u}+\frac{1}{2}\ln \left| \frac{u-1}{u+1}\right| + C $$ Finally, going back to $x$, we get $$ \sqrt{x^2+1} + \frac{1}{2}\ln \left| \frac{1-\sqrt{x^2+1}}{1+\sqrt{x^2+1}} \right|+C = \sqrt{x^2+1} + \frac{1}{2}\ln \left( \frac{\sqrt{x^2+1}-1}{\sqrt{x^2+1}+1} \right)+C $$

share|cite|improve this answer
Very clear approach +1 – Babak S. Nov 4 '13 at 13:18

$x = \tan u$

$dx = \sec^2u \,du$

Use the identity $\sec^2u = \tan^2u + 1$

$\sqrt{x^2 + 1 } = \sqrt{\tan^2(u) + 1} = \sqrt{\sec^2u} = \sec u$, $u = \tan^{-1}x$

Set up your integral with appropriate substitutions:

$$\int \csc u \sec^2 u \,du $$ $$= \int (1 + \tan^2 u)\csc u\,du $$ $$= \int \csc u + \tan^2 u \csc u\, du $$ $$= \int \csc u \,du + \int \tan u \sec u \,du $$

You can substitute again...For the integrand $\tan u \sec u$:

Let $t = \sec u, ds = \tan u \sec u$...

share|cite|improve this answer

I solved it, the expression above is equivalent to $$\int\frac {\sec\theta}{\tan\theta}d\theta + \int\sec\theta\tan\theta\ d\theta = \int\csc\theta\ d\theta + \sec\theta + C$$

And we know that $$\int\csc\theta\ d\theta = \ln|\csc\theta - \cot\theta| + C_1$$ After substituting for the original variable, we get $$\ln\left|\frac{\sqrt{1+x^2} - 1}{x}\right| + \sqrt{x^2+1} + C_2$$

share|cite|improve this answer
Nice. The only real trouble is in integrating $\csc \theta$. I think of this as coming from partial fractions, but it can also be obtained by making the magic substitution $u=\csc\theta-\cot\theta$. – André Nicolas Jan 3 '13 at 1:33
Nicely done. You should accept your answer. – 1015 Jan 3 '13 at 2:17
@AndréNicolas The substitution was introduced earlier in the text so that is why the author assumes that the reader should know the answer to $\int\csc\theta d\theta$. – Lucas Alanis Jan 3 '13 at 2:20

Add and subtract $\displaystyle{\frac{1}{x}}$ to the integrand: $$ \begin{aligned} \int\frac{\sqrt{1+x^2}-1}{x}\,\mathrm{d}x + \int\frac{\mathrm{d}x}{x}&=\ln\left|x\right| + \int \frac{\left(\sqrt{x^2+1}-1\right)\left(\sqrt{x^2 +1}+1\right)}{x\left(\sqrt{x^2 +1}+1\right)}\,\mathrm{d}x \\ &= \ln \left|x \right| + \int\frac{x}{\sqrt{x^2 + 1}+1}\,\mathrm{d}x \end{aligned} $$ Now, set $u = 1 + \sqrt{x^2 +1}$ and $x\,\mathrm{d}x = \left(u-1\right)\,\mathrm{d}u$ to obtain $$ \begin{aligned} \ln\left|x\right| + \int \frac{u-1}{u}\,\mathrm{d}u &= \ln\left|x\right| + u - \ln\left|u\right| + C_{0}\\ &=u + \ln\left|\frac{x}{u}\right| + C_{0} \\ & = \sqrt{1 + x^2} + \ln\left|\frac{x}{1 + \sqrt{1+x^2}}\right| + \underbrace{1 + C_{0}}_{C} \\ &=\sqrt{1+x^2} + \ln\left|\frac{x}{1+\sqrt{1+x^2}}\right| + C \end{aligned} $$

And we are done. :)

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.